Diagnostic guide for bruxism in primary health care in Santa Clara, Villa Clara, Cuba - Camacho-Guerrero, Lorena (2024)
Bruxism is complex in terms of conceptualization, etiology, diagnosis and treatment. The existing information about this pathology, although extensive, is very diffuse and it is difficult for Integral General Stomatology to determine which one to select to make an accurate diagnosis. Develop a diagnostic guide for bruxism in primary health care. Cross-sectional descriptive research was carried out, using qualitative and quantitative methodology, in three stages, in the period between 2019-2022. In the first stage, the shortcomings of the current diagnostic method were identified through documentary review, surveys of stomatologists and content analysis. In the second stage, through a nominal group, it was decided which of the identified aspects could not be missing from the instrument and it was designed. In the third and final stage, the guide was evaluated by specialist criteria. 14 aspects lacking in the conventional bruxism method were identified and included in a new instrument along with those that were performed correctly. The guide was approved by all specialists as a diagnostic tool for bruxism. The Guide groups the identified deficiencies, includes the main guidelines for its development, as well as a methodology for the clinical examination and another methodology for obtaining the diagnosis.